Sublingual misoprostol vs. oral misoprostol solution for induction of labor: A retrospective study - Amini, Mahdi; Wide-Swensson, Dag; Herbst, Andreas (Frontiers in Surgery, 2022)
Introduction: Induction of labor (IOL) is one of the most common obstetrical procedures, with an increasing rate. The prostaglandin E1 analogue misoprostol is frequently used as a primary method of labor induction. The optimal dose and route of administration is yet to be ascertained. Aim: To compare efficiacy and safety between a regimen of sublingually administered misoprostol and a regimen of orally administered misoprostol, with cesarean delivery as primary outcome. Methods: A retrospective study was conducted including women carrying a live, singleton fetus in a cephalic position with labor induced at >37+0 gestational weeks at Skåne University hospital, Lund, between January 1st 2013 to December 31st 2017. Data was obtained from computerized obstetrical charts. Results: Totally 2404 women were included; 974 induced with sublingual misoprostol and 1430 with oral solution. In primiparous women the cesarean delivery rate was lower in primiparous women induced with oral compared to sublingual misoprostol (20.5% vs 28.6%, p<0.001), whereas in parous women the rates did not differ significantly 4.9% vs 7.5%; NS). The increased risk of caesarean remained after controlling for potential confounding factors (adjusted odds ratio 1.49 (1.14-1.95). Women induced with sublingual misoprostol had a shorter time to vaginal delivery when compared to oral solution (primiparous median 16.7h vs 21.7h; p<0.001, parous median 9.9h vs 13.3 h; p=0.01), and a higher rate of vaginal delivery within 24 hours (primiparas 77.7% vs 63.3%, p<0.001, parous 93.2% vs 84.2%; p=0.01). Conclusion: IOL with oral misoprostol solution was associated with a significantly higher vaginal delivery rate when compared to sublingual misoprostol, whereas sublingual misoprostol was associated with a significantly shorter time from induction to vaginal delivery. Oral administration is considered the most safe and efficient administration of misoprostol, although more studies are needed to find the optimal route and dosage of misoprostol for IOL.